Performance of the operational Wansbeek-Bekker estimator for dynamic panel data models - Harris, Mark; Mátyás, L. (ROUTLEDGE, 2000)
Wansbeek and Bekker considered a new estimator for simple dynamic panel data models (where there are no exogenous variables) which involved a complex weighting matrix. An operational variant of this estimator is proposed which is applicable to the more realistic case where there are exogenous variables. Also proposed is an easy-to-compute approximation to the weighting matrix. The performance of this (these) new estimator(s) is examined, revealing very desirable small sample properties in a wide range of situations that the applied researcher is likely to encounter, especially in moderate time series length panels.